Multifunctional cationic polyurethanes designed for non-viral cancer gene therapy. (15th January 2016) - Cheng, Jian; Tang, Xin; Zhao, Jie; Shi, Ting; Zhao, Peng; Lin, Chao
Graphical abstract: Abstract: Nano-polyplexes from bioreducible cationic polymers have a massive promise for cancer gene therapy. However, the feasibility of cationic polyurethanes for non-viral gene therapy is so far not well studied. In this work, a linear cationic polyurethane containing disulfide bonds, urethane linkages and protonable tertiary amino groups was successfully generated by stepwise polycondensation reaction between 2, 2′-dithiodiethanol bis(p-nitrophenyl carbonate) and 1, 4-bis(3-aminopropyl)piperazine (BAP). We confirmed that the cationic polyurethane (denoted as PUBAP) displayed superior gene delivery properties to its cationic polyamide analogue, thus causing higher in vitro transfection efficiency in MCF-7 and SKOV-3 cells. Besides, further folate-PEGylation and hydrophobic deoxycholic acid (DCA) conjugation to amino-containing PUBAP can be conducted to afford multifunctional polyurethane gene delivery system. After optimization, folate-decorated nano-polyplexes from the PUBAP conjugated with 8 folate-PEG chains and 12 DCA residues exhibited superb colloidal stability under physiological conditions, and performed rapid uptake via folate receptor-mediated endocytosis, efficient intracellular gene release and nucleus translocation into SKOV-3 cells in vitro and in vivo. Importantly, PUBAP based polyplexes possess low cytotoxicity as a result of PUBAP biodegradability. Therefore, marked growth inhibition of SKOV-3 tumor xenografted in Balb/c nude mice was achieved with negligible side effects on the mouse health after intravenous administration of PUBAP based polyplexes with a therapeutic plasmid encoding for TNF-related apoptosis-inducing ligand. This work provides a new insight into biomedical application of bio-responsive polyurethanes for cancer therapy. Statement of significance: In this study, we have confirmed that disulfide-based cationic polyurethane presents a new non-viral vector for gene transfer and cancer gene therapy. The significance of this work includes: (1) design and synthesis of a group of novel disulfide-based cationic polyurethane by non-isocyanate chemistry; (2) comparative study of transfection activity between cationic polyurethanes and cationic polyamides; (3) feasibility of bioreducible cationic polyurethanes for in vivo cancer gene therapy.